The Observing Learning Activity Assisted by Concrete Media Improves Student's Conceptual Knowledge - Tegeh, I Made; Parwata, I Gusti Lanang Agung; Ostaviani, Bernadeth Grace (Jurnal Pendidikan Indonesia, 2020)
The purpose of this study was to examine the effect of observing learning activities assisted by concrete media in a scientific approach toward the conceptual knowledge of the fifth grade students. This study was a quasi-experiment with a post-test only control group design. The population of this study was all students of the fifth grade of Public Elementary School (SDN)  4 Cempaga and Public Elementary School (SDN) 4 Kawan. The samples were taken by purposive sampling. Conceptual knowledge data were collected by using multiple choice tests. The obtained data were analyzed by using a t-test. Based on the results of the t-test analysis, it was obtained tcount = 11. 36 while the ttable value was 2. 021. Based on tcount = 11. 36> ttable = 2. 021 then H0 was rejected. The results of the analysis prove that there are significant differences between a group of students who are taught by observing learning activities assisted by concrete media and a group of students who are taught by conventional learning. In addition, the average value of the experimental group learning outcomes is X̅ = 22. 30 which is higher than the average learning outcomes of the control group X̅ = 18. 40. From the results of the t-test analysis and the average learning outcomes, it can be concluded that the observing learning activities assisted by concrete media influence the conceptual knowledge of the fifth grade students. Therefore, observing learning activities assisted by concrete media are suitable to be applied to overcome the low conceptual knowledge of students. This finding will have implications, namely, to improve conceptual knowledge can be done by observing activities assisted by concrete media so the learning activities will be more meaningful and interesting.